The Mental Health Problems of Caregivers of Children with Cerebral Palsy at Self Help Group - Emi Wuri Wuryaningsih (NurseLine Journal, 2018)
Children with cerebral palsy (CP) have a high dependency on the activities of daily life (ADL) for a whole life. This can affect mental health and well-being of caregivers of CP. This study aimed to assess the mental health problems in caregiver of a child with CP who joined in self-help group (SHG) at Mojokerto East Java Province, focusing on depression symptoms. Using total sampling approach, the family member who has a role as caregivers of a child with CP were chosen and enrolled in a descriptive study, counted 37 respondents. The self-reporting questionnaire -20 (SRQ-20) with Cronbach alpha value 0.84 was used to measure their mental health status. SRQ-20 is also available in the Indonesia Ministry of Health's online application.This study shows that the majority caregiver role is a mother (94,6%). 40.5% caregiver has a risk of mental health problems that require counseling by a health professional. Caregiver experienced several complaints both physical, psychological, and social. Perceived physical complaints include frequent headaches (40.5%); difficulty sleeping (45.9%); indigestion is disturbed (29,7); tired easily (37.8%); and a bad taste in the stomach (40.5%). While the psychic complaints experienced by the caregiver on average feel tense, anxious or worried (37.8%); difficult to make decisions (35.1%); and found it difficult to enjoy daily activities (24.3%). There are 2 caregivers who have the idea of ​​suicide. These complaints are a form of response to stressors (caring for children with CP) which is a manifestation of signs and symptoms of mental health problems among them. These signs and symptoms indicate that caregivers are susceptible to depression, anxiety, helplessness, and despair. Caregiver of children with CP is a vulnerable population to psychiatric problems because of its role in fulfilling daily life care of a child with CP for a long time even a lifetime. Nurses can contribute to providing informational and emotional support to help the caregiver to achieve mental health and well-being.